Teacher's Pedagogic Competency in Integrating Al Qur’an Verses In Sociological Learning Processes - Masrizal Masrizal; Helmi Hasan (International Journal of Educational Dynamics, 2020)
Character education is an important form of education that teachers must do today, including sociology teachers. References to character formation for students can come from various sources and one of them is from the Koran. In learning, Alqur'an will be integrated with the learning materials. Conducting character education not only during the learning process, but starting from lesson planning to evaluation. This research was conducted to find out, whatOf course, the values ​​of the Koran are integrated by the sociology learning material teacher at SMAN 9 Padang. The method used in this research is qualitative research with the technique of collecting data through interviews and documentation.Analysis of research using Max Wertheimer's gesture. From the results of the research conducted it was found that, The values ​​of the Koran that are integrated into sociology learning at SMAN 9 Padang are very varied, including individual human life, human relations with God, human life in society and human relations with nature.